2011
DOI: 10.1186/1475-2875-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rapid diagnostic test SDFK40 (Pf-pLDH/pan-pLDH) for the diagnosis of malaria in a non-endemic setting

Abstract: BackgroundThe present study evaluated the SD Bioline Malaria Ag 05FK40 (SDFK40), a three-band RDT detecting Plasmodium falciparum-specific parasite lactate dehydrogenase (Pf-pLDH) and pan Plasmodium-specific pLDH (pan-pLDH), in a reference setting.MethodsThe SDFK40 was retrospectively and prospectively tested against a panel of stored (n = 341) and fresh (n = 181) whole blood samples obtained in international travelers suspected of malaria, representing the four Plasmodium species as well as Plasmodium negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 31 publications
5
50
1
Order By: Relevance
“…Another study that was performed at Combined Military Hospital Quetta by Ahmad et al (2003), concluded 100% OptiMAL sensitivity for both malaria species. Another study was performed in Belgium( non-endemic country for malaria ), reported sensitivity of 92.9% for the SD Bioline Malaria Ag Pf/Pan (Maltha et al, 2011) while in Korea, the researchers reported a sensitivity of RDT for P. vivax that ranged from 86.8% to 92.7% (Kim et al, 2011 ;Jang et al, 2013). The results of the present study are more or less similar in sensitivity to most of the above mentioned studies performed worldwide for malaria diagnosis.…”
Section: Discussionsupporting
confidence: 71%
“…Another study that was performed at Combined Military Hospital Quetta by Ahmad et al (2003), concluded 100% OptiMAL sensitivity for both malaria species. Another study was performed in Belgium( non-endemic country for malaria ), reported sensitivity of 92.9% for the SD Bioline Malaria Ag Pf/Pan (Maltha et al, 2011) while in Korea, the researchers reported a sensitivity of RDT for P. vivax that ranged from 86.8% to 92.7% (Kim et al, 2011 ;Jang et al, 2013). The results of the present study are more or less similar in sensitivity to most of the above mentioned studies performed worldwide for malaria diagnosis.…”
Section: Discussionsupporting
confidence: 71%
“…All P. falciparum malaria cases with parasitemia greater than 1000 trophozoites/μl of blood were detected as previously described [20]. However, almost 16% of blood stage asexual forms with parasitemia less than 1000/μl were not detected.…”
Section: Discussionmentioning
confidence: 77%
“…Lot-to-lot variation in RDTs is a well-known issue in performance, monitoring and quality control of RDTs [13,16]. As slight – but important – differences between lots such as those presently observed will probably go undetected by routine lot control procedures, efforts should be made at the level of manufacturing and post-marketing surveillance to assure equal performance of different RDT lots.…”
Section: Discussionmentioning
confidence: 99%